(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
The word "business" is an English word, and it is an entrepreneurial activity, or in other words, an activity aimed at making people profit. Business covers the relations between all participants of the market economy and includes the behavior of not only businessmen, but also consumers, hired workers, and government officials. In this case, they are synonyms of the word business, and in a certain sense, such concepts as commerce and trade are considered. In general, business is the work and activity of a person in the system of market relations.